Finding, Accessing, and Using Secondary Data for Research on Gifted Education and Advanced Academics. Issue 4 (November 2019) - Renbarger, Rachel L.; Sulak, Tracey N.; Kaul, Corina R.
Secondary data analysis can benefit researchers of advanced academics by providing large sample sizes and a variety of data on multiple topics. However, using secondary data comes with unique challenges. This article will outline how gifted education researchers can find, access, and use secondary data. Data are available on children from birth to adulthood and are typically accessed through the Inter-university Consortium for Political and Social Research (ICPSR) or the National Center for Education Statistics (NCES). The majority of data sources have public-use files available, but some sensitive data may require special permissions. This article includes examples of advanced academic research that used popular databases along with software options for utilizing available data. We conclude with considerations researchers should take into account when considering using secondary data analysis, such as computer memory and technical skills.